Terzan 5: a pristine fragment of the Bulge. (5th March 2015) - Ferraro, Francesco R.
Abstract: We have discovered that Terzan 5, a stellar system in the Galactic Bulge, harbors two stellar populations with different iron content (Δ[Fe/H] ~ 0.5 dex) and possibly different ages. Moreover, the observed chemical patterns significantly differ from those observed in any known genuine globular cluster. These evidences demonstrate that, similarly to ω Centauri in the Halo, Terzan 5 is not a globular cluster, but a stellar system that was able to retain the gas ejected by violent supernova explosions. Moreover the striking chemical similarity with the Bulge stars suggests that Terzan 5 could be the relic of one of the massive clumps that contributed (through strong dynamical interactions with other pre-formed and internally-evolved sub-structures) to the formation of the Galactic Bulge.